Biological control of crown gall disease in peach and cherry nursery plants by white stone powder based formulation (Sol Gall) of Brevibacillus spp. - KISHORE KHOSLA; RISHI MAHAJAN, ADITI SHARMA, A.K GUPTA*, DINESH SINGH (Indian Phytopathology, 2016)
Agrobacterium tumefaciens caused losses in stone fruit nurseries as present day management strategies are not satisfactorily work. In vitro analysis of the antagonistic activity of different Brevibacillus spp. towards plant tumorigenic Agrobacterium tumefaciens resulted in a selection of potential antagonistic isolates. Therefore, these isolates were tested for their efficacy in reducing gall formation in plants and under field condition either alone or in combination. Brevibacillus brevis (UHFBA-22) and B. choshinensis (UHFBA-30) mixed in 1:1 ratio (designated as UHFBA-28), showed maximum antagonistic activity (3.87cm dia. of inhibition zone) against A. tumefaciens. UHFBA-28 when applied in the form of white stone powder based formulation (Sol Gall) as seed treatment resulted in 11.11% incidence of crown gall. Root dip treatment with Sol Gall also minimized incidence of crown gall to 12.24 and 38.89 per cent as compared to 91.53 and 93.33 per cent incidence in two different experiments. However, soil drenching of nursery plants with UHFBA-28 gave complete control of crown gall disease in peaches. This treatment was comparable with other cumbersome treatments viz., soil solarization and its combination of seed treatment with UHFBA-28, and treatment of nursery soil with, formaldehyde (5%) + seed treatment with UHFBA-28.